Community Ecology of Freshwater Fish in Relation to Environmental Variables in Murum Hydroelectric Power Dam, Belaga, Sarawak - Angie, Sapis (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This study was aimed to evaluate the effects of environmental variables specifically, dam impoundment, riparian zone and water quality on the fish assemblages, growth, and their spatial shift in diet at upstream and downstream of the reservoir, as well as to document fish succession in Murum reservoir. As the impoundment of Murum reservoir starts, the stream ecosystem, type of habitats and water quality gradually change as the environment changes. Samplings were conducted from May 2014 to December 2015 at four areas located in the vicinity of Murum Dam: downstream of Murum River, Dam site, inundated areas of Pleiran River and Danum River. Water quality and fish fauna were studied. Types of land uses, riparian habitat characteristics and other environmental variables were also enumerated, and were found to be spatially and temporally different. Fish fauna samplings were carried out at 17 stations by using three-layered nets, monofilament gill net of various mesh sizes and electroshocking technique. Land use changes and degradation of riparian zone in Murum catchment were shown to have influences on water quality and eventually affecting fish communities of the newly impounded reservoir. In the case of newly impounded Murum reservoir, the two major catchments of the reservoir, Pleiran and Danum, have shown significant disturbances due to logging, forest and oil palm plantations and subsistence farming. Two-way Analysis of Variance (ANOVA) showed that there are significant differences (p<0.05) in quality of upstream and downstream waters of Murum Dam at spatial and temporal scales. A total of 8773 fish individuals representing 58 species belonging to 11 families were caught from stations below and above Murum Dam. Fish populations were dominated by the family Cyprinidae (63.6%). The highest number of species was recorded in downstream of Murum River with 34 species, followed by inundated area of Pleiran River (31 species) and the dam site (25 species). The lowest number was recorded at the inundated iv area of Danum River (23 species). Overall, Oreochromis niloticus was the most numerically abundant species (33.0%) and is widely distributed in the whole area. This is followed by Barbodes binotatus which comprised 16.8% of the total individuals caught. About 20 fish species were indicators for the whole Murum catchment at different impoundment or filling phases. Composition and assemblages of fish were influenced by fluctuation of water level, conductivity, Chl-a, and BOD5. This study also found that the growth of B. binotatus, O. niloticus, Hampala bimaculata, Barbonymus collingwoodii, and Lobocheilos falcifer varied at spatial and temporal gradients. The growth of the fish declined from positive allometric growth to negative allometric growth, throughout the impoundment and as water level fluctuates. Temperature, conductivity, pH, turbidity, dissolved oxygen, total suspended solids, Chl-a, transparency and water level are physicochemical parameters that contributed to the variation in fish growth in Murum waters. Stomach content analysis showed that H. planiceps, H. bimaculata, H. macrolepidota and C. apogon consumed a wide range of foods and Wi was highly loaded with small predators thus suggest that they are carnivores. Tor douronensis and Barbonymus schwanenfeldii are classified as omnivores. The feeding habit of O. niloticus and P. waandersi was best represented by aquatic plant, detritus and digested items and are categorised as herbivores. The results imply that conversion of forested area at riparian corridor to open area and fluctuation in water level has led to changes in physicochemical characteristics, and subsequently might have resulted in habitat partitioning by the fish species according to their environmental tolerance limit